The Impact of Formula Choice for the Management of Pediatric Cow’s Milk Allergy on the Occurrence of Other Allergic Manifestations: The Atopic March Cohort Study - Nocerino, Rita; Bedogni, Giorgio; Carucci, Laura; Cosenza, Linda; Cozzolino, Tommaso; Paparo, Lorella; Palazzo, Samuele; Riva, Luca; Verduci, Elvira; Berni Canani, Roberto (The Journal of pediatrics, 2021)
To compare the impact of different formulas on the occurrence of other atopic manifestations and the time of immune tolerance acquisition. In a 36-month prospective cohort study, the occurrence of other atopic manifestations (eczema, urticaria, asthma, and rhinoconjunctivitis) and the time of immune tolerance acquisition were comparatively evaluated in immunoglobulin E–mediated children with cow's milk allergy (CMA) treated with extensively hydrolyzed casein formula containing the probiotic L. rhamnosus GG (EHCF + LGG), rice hydrolyzed formula, soy formula, extensively hydrolyzed whey formula (EHWF), or amino acid–based formula. In total, 365 subjects were enrolled into the study, 73 per formula cohort. The incidence of atopic manifestations was 0.22 (Bonferroni-corrected 95% CI 0.09-0.34) in the EHCF + LGG cohort; 0.52 (0.37-0.67) in the rice hydrolyzed formula cohort; 0.58 (0.43-0.72) in the soy formula cohort; 0.51 (0.36-0.66) in the EHWF cohort; and 0.77 (0.64-0.89) in the amino acid–based formula cohort. The incidence of atopic manifestations in the rice hydrolyzed formula, soy formula, EHWF, and amino acid–based formula cohorts vs the EHCF + LGG cohort was always greater than the prespecified absolute difference of 0.25 at an alpha-level of 0.0125, with corresponding risk ratios of 2.37 (1.46-3.86, P < .001) for rice hydrolyzed formula vs EHCF + LGG; 2.62 (1.63-4.22, P < .001) for soy formula vs EHCF + LGG; 2.31 (1.42-3.77, P < .001) for EHWF vs EHCF + LGG; and 3.50 (2.23-5.49, P < .001) for amino acid–based formula vs EHCF + LGG. The 36-month immune tolerance acquisition rate was greater in the EHCF + LGG cohort. The use of EHCF + LGG for CMA treatment is associated with lower incidence of atopic manifestations and greater rate of immune tolerance acquisition.